2009
DOI: 10.5194/acp-9-4897-2009
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the emission and transport of pollution from wildfires using the IASI CO retrievals: analysis of the summer 2007 Greek fires

Abstract: Abstract.In this paper, we analyze the performance of the Infrared Atmospheric Sounding Interferometer (IASI), launched in October 2006 on board METOP-A, for the monitoring of carbon monoxide (CO) during extreme fire events, focusing on the record-breaking fires which devastated thousands of square kilometers of forest in Greece during the last week (23-30) of August 2007. After an assessment of the quality of the profiles retrieved using the Fast Optimal Retrievals on Layers for IASI (FORLI) algorithm, the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 50 publications
6
90
0
Order By: Relevance
“…All of the 12 month running average time series of total column CO show clear features due to changes in fire emissions such as the broad peak around 2002-2003 for NH observations due to a significant number of boreal fires (e.g., Yurganov et al, 2005) and an overall decline in global fire emissions from 2007 to 2009 as shown in the GFED3 inventory (van der Werf et al, 2010). There may also be some correlation of lower CO column to lower emissions due to the global financial crisis starting in late 2008.…”
Section: Interannual Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…All of the 12 month running average time series of total column CO show clear features due to changes in fire emissions such as the broad peak around 2002-2003 for NH observations due to a significant number of boreal fires (e.g., Yurganov et al, 2005) and an overall decline in global fire emissions from 2007 to 2009 as shown in the GFED3 inventory (van der Werf et al, 2010). There may also be some correlation of lower CO column to lower emissions due to the global financial crisis starting in late 2008.…”
Section: Interannual Variabilitymentioning
confidence: 99%
“…Global direct emissions of CO are dominated by relatively stable anthropogenic emissions (∼500-600 Tg yr−1) and by biomass burning with significant interannual variability (∼300-600 Tg yr−1), (e.g., Granier et al, 2011, van der Werf et al, 2010. Satellite observations of CO can clearly identify areas of intense burning (e.g., Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been previously conducted using remote measurements of biomass burning emissions from ACE-FTS Coheur et al, 2007) as well as other space-borne instruments Glatthor et al, 2009;Torres et al, 2009;Turquety et al, 2009). Rinsland et al (2005) first explored the possibility of using ACE-FTS to study the emission of longer lived primary pyrogenic species and their long-range transport to establish the effectiveness of ACE-FTS in measuring the emission of trace species from biomass burning.…”
Section: K a Tereszchuk Et Al: Ace-fts Observations Of Pyrogenic Tmentioning
confidence: 99%
“…The CO total columns have been validated for different locations and atmospheric conditions (e.g., De Wachter et al, 2012;Kerzenmacher et al, 2012), and the comparisons with other data have shown good overall agreement, even if some discrepancies were found within COenriched plumes (reaching 12 % over the Arctic in summer, see Pommier et al, 2010; and reaching 17 % in comparison with other IR sounders, see George et al, 2009). These data were also used previously to study biomass burning plumes (e.g., Turquety et al, 2009;Pommier et al, 2010;Krol et al, 2013;Whitburn et al, 2015).…”
Section: The Co Retrieval Characteristicsmentioning
confidence: 83%